Virulence differences among Sclerotinia sclerotiorum isolates determines host cotyledon resistance responses in Brassicaceae genotypes - Ge, Cynthia; You, M.; Barbetti, M. (Kluwer Academic Publishers, 2015)
Differences in Sclerotinia rot (SR) disease severity, caused by two categorized pathotypes and one more recent isolate of S. sclerotiorum and measured in terms of cotyledon lesion diameter, were studied across diverse Brassicaceae hosts to characterize host response and pathogen virulence. There were significant differences (P =0.001) between genotypes, isolates and a significant genotype x isolate interaction. The mean diameter of cotyledon lesions ranged from 5 mm in the most resistant genotypes (e.g., Brassica juncea Ringot I and Seeta) to = 13.6 mm in the most susceptible genotypes (e.g., B. tournefortii Wild turnip #1 and #2, Sisymbrium irio London rocket Wild #1 and #2, and B. nigra 4381). Responses, in at least one experiment for some B. juncea (e.g., Seeta, Ringot I) and Raphanus sativus (e.g., Colonel) genotypes, were generally highly resistant irrespective of the isolate used, making them ideal sources of resistance to exploit for developing new varieties with more effective resistance to SR across multiple pathotypes of this pathogen. In contrast, some other genotypes showed significant isolate dependency, with high levels of resistance against one isolate (e.g., B. napus Charlton against the WW4 isolate; B. napus Oscar against the ‘Cabbage’ isolate) but quite susceptible to other isolates (e.g., B. napus Charlton against the ‘Cabbage’ and MBRS1 isolates; B. napus Oscar against the WW4 isolate). These findings highlight the value from using pathotypes of different physiological specialization in screening programs to identify host resistance that is durable across multiple pathotypes. Distinct host resistance symptom types were reported for the first time on some genotypes against isolate WW4; including a distinct yellow halo observed around lesions on B. napus RQ001, indicative of leaf senescence involved in programmed cell death (PCD); a distinct dark brown margin observed around lesions on R. sativus, indicative of a hypersensitive response (HR); and the HR ‘flecking’ on Sinapis alba Concerta and B. juncea Seeta. That WW4 was the most pathogenic isolate for genotypes such as B. juncea Hetianyoucai and B. napus Oscar that showed high level resistance to the ‘Cabbage’ isolate and intermediate resistance to MBRS-1, dispels previously held views that WW4 was a largely avirulent pathotype of little consequence. Rather, isolate WW4 offers unique opportunities to investigate HR and PCD host resistance responses to S. sclerotiorum in Brassicaceae.